2010
DOI: 10.3945/ajcn.2010.29302
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in infancy and long-term risk of obesity: evidence from 2 randomized controlled trials

Abstract: In 2 prospective randomized trials, we showed that a nutrient-enriched diet in infancy increased fat mass later in childhood. These experimental data support a causal link between faster early weight gain and a later risk of obesity, have important implications for the management of infants born small for gestational age, and suggest that the primary prevention of obesity could begin in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 48 publications
3
143
0
Order By: Relevance
“…The timing of infancy weight gain is another issue that may impact future overweight. Singhal et al (35) have demonstrated a causal link between rapid early weight gain and the future risk for obesity. Finally, breast-feeding compared with formula-feeding positively impacts the digestive tract, leading to immediate and long-term health effects.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of infancy weight gain is another issue that may impact future overweight. Singhal et al (35) have demonstrated a causal link between rapid early weight gain and the future risk for obesity. Finally, breast-feeding compared with formula-feeding positively impacts the digestive tract, leading to immediate and long-term health effects.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in weight for length at 2 years is of major benefit as it predicts a 13 % lower obesity risk at age 14-16 years with lower protein infant formula (14) . Longterm follow-up of a subset of children assigned in other trials to nutrient-dense or less nutrient-dense infant formulae found that those infants who received the growth promoting formulae had increased body fat mass 5-8 years later (41) . Moreover, in several non-randomised analyses, faster weight gain in infancy was associated with greater fat mass in childhood (30,32,33,40) .…”
Section: Accelerated Postnatal Growth Hypothesismentioning
confidence: 99%
“…Thus, early nutritional practices have not been backed by rigorous experimental evidence of efficacy and safety, which is expected in other areas of public health; and have the potential to cause harm. For example, 'intuitive' attempts to promote growth in small, growth-retarded newborns could significantly increase later CVD and obesity (3)(4)(5)(8)(9)(10)(11)(12)(13)(14) . This lack of a sound evidence-base has prevented changes to nutritional and public health practice in infancy in order to prevent later NCD.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%